Intra-aortic balloon pump use in out-of-hospital cardiac arrest patients who underwent extracorporeal cardiopulmonary resuscitation. (January 2023) - Kashiura, Masahiro; Kishihara, Yuki; Ozawa, Hidechika; Amagasa, Shunsuke; Yasuda, Hideto; Moriya, Takashi
Abstract: Aim: To investigate the effect of intra-aortic balloon pump (IABP) use after extracorporeal membrane oxygenation-assisted cardiopulmonary resuscitation (ECPR) on short-term neurological outcomes and survival in patients with out-of-hospital cardiac arrest (OHCA). Methods: We retrospectively analysed data collected between June 2014 and December 2019 from the Japanese OHCA registry. Adult patients (aged ≥18 years) who underwent ECPR were included. We divided the patients into those who received IABP and those who did not receive IABP. The primary outcome was the 30-day favourable neurological outcomes in survived patients. The secondary outcome was the 30-day survival. We performed propensity score matching (PSM) to adjust for confounding factors after multiple imputations of missing data. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were estimated using logistic regression analysis after PSM to adjust for confounding factors after IABP initiation. Results: Among 2135 adult patients who underwent ECPR, 1173 received IABP. In 842 matched patients, IABP use was associated with survival (aOR, 1.98; 95% CI, 1.39–2.83; p  < 0.001). However, IABP use was not significantly associated with the 30-day neurologically favourable outcome in 190 survived patients (aOR, 1.22; 95% CI, 0.79–1.89; p  = 0.36). Conclusion: The use of IABP in patients with OHCA who underwent ECPR was associated with 30-day survival. Among survived patients, there was no significant association between IABP use and 30-day neurological outcome. A further well-designed prospective study is needed.